Non-coding rnas in Turner syndrome: a systematic review - Júlio César Carvalho de Oliveira; Eldevan da Silva Barbosa; Nathaniel Batista Silva; Thaís da Conceição Silva; Ana Gabrielly de Melo Matos; Jaqueline Diniz Pinho (Revista Paulista de Pediatria)
ABSTRACT Objective: The aim of this study was to summarize the main findings of non-coding RNA (ncRNAs) in Turner syndrome (TS), correlating these biomolecules with the clinical manifestations in affected patients. Data source: Searches were conducted in the databases of the United States National Library of Medicine (PubMed), Scientific Electronic Library Online (SciELO), and ScienceDirect, covering original English articles published from 2014 to 2023. Descriptors used included "lncRNAs and Turner Syndrome," "miRNAs and Turner Syndrome," and "circRNAs and Turner Syndrome." The studies that were included addressed the role of ncRNAs in the clinical characteristics of patients with TS. Exclusion criteria comprised texts in abstracts, reports, reviews, and monographs. Data synthesis: We identified 147 studies, of which seven were included. In the analysis of microRNAs, miR-486-5p and miR-320a stood out, being associated with ovarian development; miR-126-3p and miR-126-5p were related to greater aortic stiffness. Regarding long non-coding RNAs, the downregulation of XIST indicated dysfunctions in X chromosome inactivation. Concerning circular RNAs, circPPP2R3B, circCSF2RA, and circPCTN were related to immunological functions, while circ_0090421, circ_0090392, and circ_0089945 were linked to cardiac development. Conclusions: The data from these studies demonstrate that these biomolecules play crucial roles in processes related to specific characteristics observed in TS patients. Besides being suggested as potential biomarkers, they may be useful in clinical practice.